A complex regulatory network governs the expression of symbiotic genes in Sinorhizobium fredii HH103 - Navarro-Gómez, Pilar; Fuentes-Romero, Francisco; Pérez-Montaño, Francisco; Jiménez-Guerrero, Irene; Alías-Villegas, Cynthia; Ayala-García, Paula; Almozara, Andrés; Medina, Carlos; Ollero, Francisco-Javier; Rodríguez-Carvajal, Miguel-Ángel; Ruiz-Sainz, José-Enrique; López-Baena, Francisco-Javier; et al. (Frontiers in Plant Science, 2023)
The establishment of the rhizobium-legume nitrogen-fixing symbiosis relies on the interchange of molecular signals between the two symbionts. We have previously studied by RNA-seq the effect of the symbiotic regulators NodD1, SyrM, and TtsI on the expression of the symbiotic genes (the nod regulon) of Sinorhizobium fredii HH103 upon treatment with the isoflavone genistein. In this work we have further investigated this regulatory network by incorporating new RNA-seq data of HH103 mutants in two other regulatory genes, nodD2 and nolR. Both genes code for global regulators with a predominant repressor effect on the nod regulon, although NodD2 acts as an activator of a small number of HH103 symbiotic genes. By combining RNA-seq data, qPCR experiments, and β-galactosidase assays of HH103 mutants harbouring a lacZ gene inserted into a regulatory gene, we have analysed the regulatory relations between the nodD1, nodD2, nolR, syrM, and ttsI genes, confirming previous data and discovering previously unknown relations. Previously we showed that HH103 mutants in the nodD2, nolR, syrM, or ttsI genes gain effective nodulation with Lotus japonicus, a model legume, although with different symbiotic performances. Here we show that the combinations of mutations in these genes led, in most cases, to a decrease in symbiotic effectiveness, although all of them retained the ability to induce the formation of nitrogen-fixing nodules. In fact, the nodD2, nolR, and syrM single and double mutants share a set of Nod factors, either overproduced by them or not generated by the wild-type strain, that might be responsible for gaining effective nodulation with L. japonicus.